Case of acute hepatic injury and elevated ethanol levels in a non-alcoholic adult. Issue 11 (10th November 2019) - Albano, Jeri; Patarroyo - Aponte, Gabriel Dario; Mahmood, Ejaz
Abstract : Blood ethanol concentration is measured using different techniques. Gas chromatography/mass spectrometry is used in forensic laboratories to measure whole blood ethanol levels while enzyme immunoassay is often used in hospitals to measure serum or plasma ethanol levels. Lactic acidosis can theoretically cause false elevation of blood ethanol levels measured through enzymatic assay because this method measures the reduction of nicotinamide adenine dinucleotide (NAD+) to nicotinamide adenine dinucleotide- hydrogen (NADH) via the action of a dehydrogenase. Here, we present a rare incidence of ethanol level elevation in a non-alcoholic adult male secondary to lactic acidosis from a rare form of large B-cell lymphoma with infiltration of the liver.